Accumulation and Precipitation of Cu and Zn in a Centenarian Vineyard. Issue 2 (8th March 2019) - Bortoluzzi, Edson Campanhola; Korchagin, Jackson; Moterle, Diovane Freire; dos Santos, Danilo Rheinheimer; Caner, Laurent
Abstract : Core Ideas: The study highlights soil geochemical‐mineralogical alteration due to Cu‐based fungicide application. Copper enrichment reached 26 times greater in vine rhizosphere than in the control site. Copper precipitation at high soil pH favors mineral formation in the vine rhizosphere. Vineyard areas have received remarkable amounts of Cu‐based fungicides and organic waste, causing metals to accumulate in the soil profile. The objective of this study was to determine the different chemical forms of Cu and Zn in a centenarian vineyard soil and discuss the formation of Cu‐ and Zn‐bearing minerals in the clay fraction. For this, a Brazilian Inceptisol planted with vines (123‐yr‐old vineyard) was sampled in (i) the vine rhizosphere (RV), (ii) the middle of the plant row (MPR), and (iii) under a natural forest site (F) (control treatment). The amounts of total, exchangeable and residual Cu forms in the RV reached 4500, 1400, and 600 mg kg ‐1, respectively. The chemical enrichments of Cu and Zn in RV were 26 and 2.8 times greater than those in the F site, respectively. Peaks were observed on the X‐ray diffraction (XRD) patterns in the clay fraction from the RV site that were compatible with Cu‐bearing minerals. The mineralogical results are potentially and broadly significant to highlight the mechanisms of co‐precipitation of toxic ions in soils where fungicides were applied. A centenarian vineyard that received high amounts of Cu‐based fungicide accumulated Cu in the rhizosphere zone, had favorable conditions (i.e., high metal and pH levels) for the occurrence of Cu‐bearing minerals. Furthermore, long‐term traditional agriculture practices should be revisited to avoid environmental contamination.